Endemic Kaposi’s sarcoma in a HIV-negative patient - José Revilla-López; Raúl Mendoza-Fabián; Andrea Anampa-Guzmán; Josias Rosales-Zúñiga; Joel Chalco-Huamán (Revista Peruana de Medicina Experimental y Salud Pública, 2015)
Kaposi’s sarcoma (KS) is a multicentric, inflammatory angioproliferative cancer associated with herpes virus 8 (HHV-8). It has four clinico-epidemiological types: classic, endemic, iatrogenic and epidemic, or HIV associated. Clinically it may be indolent or aggressive, mainly affecting mucocutaneous areas with eventual visceral and lymph node involvement. It is often present and in a more aggressive form in the HIV-positive population. We report a case of a 27-year-old HIVnegative male patient with a bleeding tumoral lesion in the Waldeyer ring, multiple lymphadenopathies and exophytic foot lesions that remit with anthracycline-based emergency chemotherapy. HIV-negative KS is a rare condition. It is important to consider Peru as an endemic region for HHV-8. The oral involvement of KS is a rare manifestation and of poor prognosis, however, the HIV-negative factor could confer a good prognosis.